Dryland restoration successes in the Sahel and Greater Horn of Africa show how to increase scale and impact - Reij, C.; Pasiecznik, N.; Mahamoudou, S.; Kassa, H.; Winterbottom, R.; Livingstone, J. (2020)
Drylands occupy more than 40% of the world’s land area and are home to some two billion people. This includes a disproportionate number of the world’s poorest people, who live in degraded and severely degraded landscapes. The United Nations Convention to Combat Desertification states on its website that 12 million hectares are lost annually to desertification and drought, and that more than 1.5 billion people are directly dependent on land that is being degraded, leading to US$42 billion in lost earnings each year. In Africa, three million hectares of forest are lost annually, along with an estimated 3% of GDP, through depleted soils. The result is that two-thirds of Africa’s forests, farmlands and pastures are now degraded. This means that millions of Africans have to live with malnutrition and poverty, and in the absence of options this further forces the poor to overexploit their natural resources to survive. This in turn intensifies the effects of climate change and hinders economic development, threatening ecological functions that are vital to national economies.